Household consumption, household indebtedness, and inequality in Turkey: A microeconometric analysis - Özlem Albayrak (Levy Economics Institute of Bard College, 2020)
This paper examines whether relative income and income inequality within reference groups affect household consumption. Using the explanations of consumption behavior based on Dusenberry's relative income hypothesis, we test if household consumption levels in Turkey are affected by the household's relative position and inequality in the reference group between 2005-12 by employing cross-sectional household-level data. We find that household consumption is negatively related to the relative income indicator after controlling for absolute income, and positively related to the income inequality of the reference group, as the literature suggests. The paper also shows that household indebtedness has a positive impact on household consumption when inequality in the reference group and the relative position of households are controlled for. We confirm that the results are not sensitive to chosen relative income indicators and income inequality.
Keywords: D12; D63; G51; 330; Consumer Behavior; Inequality; Relative Income Hypothesis; Household Debt